Informality, Development, and the Business Cycle in North Africa - Cardarelli, Roberto (Departmental Papers; Departmental Paper ;, 2022)
North African economies are characterized by a significant share of informal activity and employment. About two-thirds of workers in North Africa operate without any formal arrangement and social protection, and about 30 percent of GDP is estimated to be produced by informal workers and firms. This paper finds that while a few key structural characteristics could explain "normal" informality in North Africa, policy distortions explain a large share of excess informality. Among the structural factors that can lead to high informality, the relatively lower level of human capital and younger population help explain the high informality in the region, as low-skilled and young people generally find it more difficult to operate in the formal sector. At the same time, gaps in a set of policy indicators also explain the relatively high informality in North Africa. In particular, this paper finds that gaps in the quality of governance explain about half of the excess informality experienced in North Africa compared with advanced economies. In this context, the expansion of the informal sector in Algeria and Tunisia from the mid-2000s partially reflects the deterioration in a few indicators of their governance and regulatory frameworks. In contrast, the decline in informality observed in Egypt, Mauritania, and Morocco over this period also reflects improved business regulations, governance, and tax systems, in addition to continued progress in economic development. While informality has traditionally buffered regional labor markets against the impact of recessions, the COVID-19 crisis has been different. North African economies have generally exhibited relatively stable unemployment rates, including during recessions, largely owing to their high levels of informality. However, informal employment has fallen significantly in North Africa during the pandemic, as lockdown measures have particularly affected high-informality service sectors. As the pandemic subsides and the lockdown measures are removed, the recovery of regional labor markets could exhibit a stronger-than-usual rebound of informal employment. Ensuring an inclusive recovery from the pandemic would call for renewed efforts to construct more modern (digitalized), more efficient, and fairer systems of social protection, building on the progress achieved in the region during the pandemic in extending safety nets to informal workers.